Analisis Kesulitan Terhadap Penyusunan Proposal Penelitian Pada Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Medan (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research is to find out the difficulties faced by students in preparing research proposals for Indonesian language and literature education. This type of research is descriptive qualitative with research subjects being students of the Indonesian language and literature education study program. Data collection methods in this study are observation, interviews, and documentation. The data analysis technique follows the Miles and Huberman model which includes data collection, data reduction, data display, and drawing conclusions. The results of the study indicate that many have difficulty defining problems in writing research proposals and formulating the benefits of a research. In some cases the activity proposal text is rejected because the content and objectives in the text are unclear and unconvincing (could be due to structure or written language) which seems not optimal) so that the authorities hesitate to accept it. Student difficulties as illustrated by the results of the questionnaire indicate that students still need to be given more information.